PENGARUH TEKNOLOGI INFORMASI TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - Dyah Pravitasari (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2012)
In this research show if the use of Information System Technology must do by auditor. As auditor trusted by sosieties, Public Accountan Office should use otimally the ability so that this matter be ethic duties which carry by public accountants as the third side whom believe to do the audite, which the result not only for client, but for user to the financial report. So that Public Accontant Office can raise effisiency and effectively audit process and their qualitis of the audit. Way that can reach is by raises ability and undertanding auditor in use of information tecnology for aditor to finish their jobs. Result cooefisience multiply (R2) is 0.430 give clue if contribution The Influence Knowledge Of Information Technology To Auditor Performance On Public Accountant Office In Surabaya have range is enough tight is 43%. Result of F test get F value is 8.154 with significant level 0.000 show significant which is getmore lowerthan 0.05 it mean H0 is rejected to level of significant 5%. It mean that The Influence Knowledge Of Information Technology To Auditor Performance On Public Accountant Office In Surabaya at simultant influence positive significant to auditor performance.